A Review of Knowledge, Practice and Perceived Health Effect on Domestic Waste Disposal in Nigeria - Kolawole Aisha Tolani (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Domestic waste disposal is a critical component of environmental sanitation and a key determinant of public health outcomes, particularly in developing countries. Domestic waste refers to solid and semi-solid materials generated from households through routine daily activities such as cooking, cleaning, personal hygiene, and general household maintenance. Objective: This study aims to assess the knowledge, practice, and perceived health effects of domestic waste disposal in Nigeria. Findings: Improper domestic waste disposal remains a major public health challenge in Nigeria, particularly in urban and semi-urban areas. Practices such as the indiscriminate dumping of refuse in open spaces, drainage channels, and unapproved dumpsites, as well as the open burning of household waste, are still common despite existing government policies and environmental sanitation programmes. These improper practices contribute to environmental pollution, blocked drainage systems, flooding, and the proliferation of disease vectors, exposing residents to sanitation-related diseases, particularly vector-borne and waterborne infections. Empirical studies have consistently demonstrated a strong association between poor knowledge of domestic waste disposal, unsafe disposal practices, and increased prevalence of sanitation-related diseases. Conclusion: The literature reviewed indicates that improper domestic waste disposal remains a major public health challenge and that knowledge plays a vital role in preventing waste-related diseases. This study provides baseline information on residents' knowledge of domestic waste disposal and its associated health implications, which will be beneficial to public health authorities, environmental health officers, and policymakers in designing effective waste management policies and health education programmes.